Separate N‐acetyl aspartyl glutamate, N‐acetyl aspartate, aspartate, and glutamate quantification after pediatric mild traumatic brain injury in the acute phase. Issue 6 (16th June 2020) - Menshchikov, Petr; Ivantsova, Anna; Manzhurtsev, Andrei; Ublinskiy, Maxim; Yakovlev, Alexey; Melnikov, Ilya; Kupriyanov, Dmitrii; Akhadov, Tolib; Semenova, Natalia
Abstract : Purpose: To separately measure N‐acetyl aspartul glutamate (NAAG), N‐acetyl aspartate (NAA), aspartate (Asp), and glutamate (Glu) concentrations in white matter (WM) using J‐editing techniques in patients with mild traumatic brain injury (mTBI) in the acute phase. Methods: Twenty‐four patients with closed concussive head injury and 29 healthy volunteers were enrolled in the current study. For extended 1 H MRS examination, patients and controls were equally divided into two subgroups. In subgroup 1 (12 patients/15 controls), NAAG and NAA concentrations were measured in WM separately with MEGA‐PRESS (echo time/repetition time [TE/TR] = 140/2000 ms; δ ON NAA / δ OFF NAA = 4.84/4.38 ppm, δ ON NAAG / δ OFF NAAG = 4.61/4.15 ppm). In subgroup 2 (12 patients/14 controls), Asp and Glu concentrations were acquired with MEGA‐PRESS (TE/TR = 90/2000 ms; δ ON Asp / δ OFF Asp = 3.89/5.21 ppm) and TE‐averaged PRESS (TE from 35 ms to 185 ms with 2.5‐ms increments; TR = 2000 ms) pulse sequences, respectively. Results: tNAA and NAAG concentrations were found to be reduced, while NAA concentrations were unchanged, after mild mTBI. Reduced Asp and elevated myo‐inositol (mI) concentrations were also found. Conclusion: The main finding of the study is that the tNAA signal reduction in WM after mTBI is associated with a decrease in the NAAG concentration rather than a decrease in the NAA concentration, as was thought previously. This finding highlights the importance of separating these signals, at least for WM studies, to avoid misinterpretation of the results. NAAG plays an important role in selectively activating mGluR3 receptors, thus providing neuroprotective and neuroreparative functions immediately after mTBI. NAAG shows potential for the development of new therapeutic strategies for patients with injuries of varying severity.